2008
DOI: 10.1111/j.1365-2036.2008.03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: the effects of a fermented milk product containing Bifidobacterium lactis DN‐173 010 on abdominal distension and gastrointestinal transit in irritable bowel syndrome with constipation

Abstract: SUMMARY BackgroundA sensation of abdominal swelling (bloating) and actual increase in girth (distension) are troublesome features of irritable bowel syndrome (IBS), which is more common in patients with constipation, especially those with delayed transit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
250
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(267 citation statements)
references
References 58 publications
10
250
0
7
Order By: Relevance
“…Second, these anaerobic bacterias produce organic acid due to fermented sugar, make the PH value decreased and stimulate peristalsis to improve the intestinal fermentation process. Finally changed the microenvironment, and feces easy to be excreted (Abrams et al, 1967;Agrawal et al, 2009). …”
Section: Efficacy Of Bifidobacterium Tetragenous Viable Bacteria Tablmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, these anaerobic bacterias produce organic acid due to fermented sugar, make the PH value decreased and stimulate peristalsis to improve the intestinal fermentation process. Finally changed the microenvironment, and feces easy to be excreted (Abrams et al, 1967;Agrawal et al, 2009). …”
Section: Efficacy Of Bifidobacterium Tetragenous Viable Bacteria Tablmentioning
confidence: 99%
“…After cancer patients were treated by chemotherapy, some factors acted in vivo destroyed the intestinal microorganisms of cancer patients (De Paula et al, 2008;Blokhina et al, 2011;Zhan et al, 2012). The number of bifidobacteriums and other anaerobic bacteria drops, oligosaccharides accumulated in the intestine due to the short of bifidobacteriu (Agrawal et al, 2009;Lu et al, 2013). And the symptoms, eg., abdominal distension, abdominal pain, defecation discomfort, etc.…”
Section: Efficacy Of Bifidobacterium Tetragenous Viable Bactermentioning
confidence: 99%
“…Agrawal et al reported that it was necessary to select an organism or a mixture of probiotics that exhibit the properties most suitable for the particular expected health benefit or physiological effect. 15 In a study by Choi SC, et al it was observed that probiotic fermented milk containing dietary fiber was more effective particularly in those patients with the constipation-predominant IBS. 16 The said study confirmed the available evidence that fiber appears to play a role in the management of patients with IBS, especially if constipation is the primary concern.…”
Section: -14mentioning
confidence: 99%
“…Bifidobacterium lactis DN-173 010 (Activia ® , Dannon, White Plains, NY) was shown to be efficacious in a female IBS-C population [78] and a healthy population with digestive symptoms [79,80]. A randomized, double-blind, controlled study examined the efficacy of fermented milk-containing B lactis DN-173 010 administered twice daily for 4 weeks in females with IBS-C (n = 34) who experienced bloating at least twice weekly [78].…”
Section: Bifidobacterium Lactis Dn-173 010mentioning
confidence: 99%
“…A randomized, double-blind, controlled study examined the efficacy of fermented milk-containing B lactis DN-173 010 administered twice daily for 4 weeks in females with IBS-C (n = 34) who experienced bloating at least twice weekly [78]. Compared with patients who received a control solution, patients who received B lactis had an improvement from baseline in median percentage change of maximal abdominal distension (P = 0.02), decreases in orocecal (P = 0.049) and colonic (P = 0.03) transit times, and reduced intensity of IBSrelated abdominal pain/discomfort (P = 0.04) and global IBS symptoms (P = 0.03) after 4 weeks of treatment.…”
Section: Bifidobacterium Lactis Dn-173 010mentioning
confidence: 99%